Microsoft Visual Basic 2010 introductory : for Windows applications - Shelly, Gary B. (Boston, Massachusetts : Course Technology Cengage Learning, 2011)
MICROSOFT VISUAL BASIC 2010 FOR WINDOWS AND MOBILE APPLICATIONS, INTRODUCTORY teaches students the essentials of computer programming using the latest Visual Basic programming language, Visual Basic 2010.